BSCI-13. TUMOR-SPECIFIC tGLI1 TRANSCRIPTION FACTOR MEDIATES BREAST CANCER BRAIN METASTASIS VIA ACTIVATING METASTASIS-INITIATING CANCER STEM CELLS AND ASTROCYTES IN THE TUMOR MICROENVIRONMENT. (12th August 2019) - Sirkisoon, Sherona; Carpenter, Richard; Rimkus, Tadas; Doheny, Daniel; Zhu, Dongqin; Aguayo, Noah; Anguelov, Marlyn; Arrigo, Austin; Regua, Angelina; Xing, Fei; Chan, Michael; Metheny-Barlow, Linda; et al.
Abstract: Breast cancer is the second leading cause of brain metastases in women; patients with breast cancer brain metastasis (BCBM) survive only 6–18 months after diagnosis. Mechanisms for BCBM remain unclear, which contributes to ineffective treatments and dismal prognosis. Truncated glioma-associated oncogene homolog 1 (tGLI1) belongs to the GLI1 family of zinc-finger transcription factors and functions as a tumor-specific gain-of-function mediator of tumor invasion and angiogenesis. Whether tGLI1 plays any role in metastasis of any tumor type remains unknown. Using an experimental metastasis mouse model, via intracardiac implantation, we showed that ectopic expression of tGLI1, but not GLI1, promoted preferential metastasis to brain. Conversely, selective tGLI1 knockdown using tGLI1-specific antisense oligonucleotides led to decreased brain metastasis of intracardially inoculated breast cancer cells. Furthermore, intracranial implantation mouse study revealed tGLI1 enhanced intracranial colonization and growth of breast cancer cells. Immunohistochemical staining of patient samples showed that tGLI1, but not GLI1, was increased in lymph node metastases compared to matched primary tumors, and that tGLI1 was expressed at higher levels in BCBM specimens compared to primary tumors. Whether tGLI1 plays any role in radioresistance is unknown; we found radioresistant BCBM cell lines and patient specimens expressed higher levels of tGLI1 than radiosensitive counterparts, and that tGLI1 promotes radioresistance. Since cancer stem cells (CSCs) are highly metastatic and radioresistant, we examined whether tGLI1 promotes BCBM and radioresistance through activating CSCs. Results showed that tGLI1 transcriptionally activates stemness genes CD44, Nanog, Sox2, and OCT4, leading to stem cell activation. Furthermore, we observed that tGLI1-positive CSCs strongly activated and interacted with astrocytes, the most abundant brain tumor microenvironmental cells known to promote tumor growth, in vitro and in vivo . Collectively, our findings establish a novel role of that tGLI1 plays in promoting breast cancer preferential metastasis to brain, radioresistance, and astrocytes in the metastatic niche.